Open Innovation Models in Research Institutes– Perspectives from India - Verma, Pranav Kumar (2009)
Open Innovation model was suggested by Dr. Henry W. Chesbrough as an important way for IP exchanges during the time of product development. This research tries to look into the same aspect of Open Innovation in the perspective of the academic institutions and analyze their benefits that get related to this system. Open Innovation model is further dependent on other proposed theories like the innovation systems NIS and RIS. Since this research tries to focus on the Indian region, hence the discussion is completely based on the Indian platform and thus the results are also based on the same. The research revolves around two important focal institutions, National Institute of Technology, Jamshedpur and Indian Institute of Science, Bangalore. Both the institutes are analyzed based on the parameters suggested by the Open Innovation model. To get the details of the information exchange that would impact the Open Innovation process, some of the related organizations related to them have been considered. Being based on the information available from people interviewed in the mentioned organizations, this research take a complete qualitative form of evaluation and interpretation of the information thus received.